PENGARUH ALOKASI DANA DESA DAN POTENSI DESA TERHADAP MANAJEMEN KEUANGAN DESA - Tehupuring, Ronald; Suhadarliyah, Suhadarliyah; Amelia, Dahlia (ANALISIS, 2023)
The phenomenon of misuse of village funds by village governments in several regions in Indonesia shows the poor management of village finances. In addition, the village government needs to manage village potential, so that better village financial management is achieved. Therefore, this study aims to examine and analyze the effect of village fund allocation and village potential on village financial management. The sample for this study uses all provincial governments in Indonesia through a purposive sampling method which reports village financial data for 2017-2020. The ordinary least squares (OLS) regression method was used in this study to test the hypothesis with the help of eviews version 12. The results of this study found that village fund allocation had a positive and significant effect on village financial management. However, village potential has no significant effect on village financial management